Negosiasi Peran dan Kecemasan Akademik: Studi Sosiologis Mahasantri Tahfiz dalam Menghadapi Beban Ganda - Fikria Az-Zahra; Muh Hanif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the academic anxiety experienced by students enrolled in an intensive Quran memorization (tahfiz) program due to the conflict between strict memorization targets and conventional academic demands. As students are required to fulfill dual responsibilities as university learners and Quran memorizers, they often face challenges in managing time, energy, and academic expectations. The study aims to explain how students negotiate these overlapping roles, map the social relationships that influence their daily experiences, and analyze the implications of intensive religious education on their psychological well-being. The research employs an educational phenomenology approach to understand participants’ lived experiences in depth. Data were collected through non-participatory observation, in-depth interviews, and documentary analysis of schedules, memorization records, and institutional documents. The findings reveal that students experience considerable psychological pressure arising from rigid time management, demanding memorization targets, and academic performance requirements. Evidence from daily activity schedules and memorization logbooks indicates that these demands often contribute to stress and academic anxiety.However, the study also finds that strong social support from supervisors, peers, and family members plays a crucial role in reducing anxiety and enhancing students’ resilience. The study concludes that intensive tahfiz programs effectively cultivate religious discipline and commitment, but they may become counterproductive if not accompanied by integrated academic workload management, flexible learning strategies, and a sustainable social support system that promotes students’ overall well-being.